Pemberdayaan Masyarakat Melalui Penumbuhkembangan Polindes Bagi Masyarakat Miskin Di Pedesaan - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
Abstract: Background and Method: The objective of this study is the community empowerment through the development of polindes for the poor community in villages in the framework of making pregnancy safer. The samples are selected purposively